1974
DOI: 10.1111/j.1440-1827.1974.tb00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Foamy Histiocytes in the Spleen Associated With Idiopathic Thrombocytopenic Purpura

Abstract: Six spleens removed from patients with idiopathic thrombocytopenic purpura (ITP) have been examined light and electron microscopically. Foamy histiocytes were found either scatterlngly or in clusters in two cases, and myelin structures were demonstrated in these foamy cells. Various stages of platelet phagocytosis and their intracellular degradation were recognized in the macrophages. These findings support the concept that the appearance of foamy cells in ITP spleens is a result of enhanced destruction of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…SIMON and PICTET (1964), in their TEM study of non-perfused rat spleen, reported the occurrence of numerous platelets within the sinus as well as in the cordal spaces, a few of which were phagocytosed by the "reticulum cells" (see also TISCHENDORF,1969). The studies of idiopathic thrombocytopenia recently indicate that in this auto-immune disorder, platelets are rapidly destroyed and cleared in the spleen (KARPATKINS, GARZ and SISKIND, 1971) and this is attained by the phagocytotic activity of splenic macrophages against antibody-coated platelets (ISHIHARA, MATSUMOTO and UCHINO, 1974). WEISS (1974) first visualized the splenic platelets under the SEM.…”
Section: Billroth Cordmentioning
confidence: 99%
“…SIMON and PICTET (1964), in their TEM study of non-perfused rat spleen, reported the occurrence of numerous platelets within the sinus as well as in the cordal spaces, a few of which were phagocytosed by the "reticulum cells" (see also TISCHENDORF,1969). The studies of idiopathic thrombocytopenia recently indicate that in this auto-immune disorder, platelets are rapidly destroyed and cleared in the spleen (KARPATKINS, GARZ and SISKIND, 1971) and this is attained by the phagocytotic activity of splenic macrophages against antibody-coated platelets (ISHIHARA, MATSUMOTO and UCHINO, 1974). WEISS (1974) first visualized the splenic platelets under the SEM.…”
Section: Billroth Cordmentioning
confidence: 99%
“…Saltzstein (1961) reported an accumulation of lipid in the histiocytes of the spleens in 7 patients with thrombocytopenic purpura. Landing et a1 (1961) Ishihara et al 1974).…”
mentioning
confidence: 99%
“…In fact, Niemann-Pick Disease type F subgroup, which is seen in adults, has also been termed "sea-blue histiocytosis" [25]. Another subset of diseases that may accompany SBHS are related to high rates of intramedullary cell death, such as chronic myelogenous leukemia [26,27], severe auto-immune neutropenia and idiopathic thrombocytopenic purpura [28][29][30][31][32][33] or, less frequently, haematological conditions such as thalassemia [34], sickle-cell anemia [7], erythemic myelosis [35], mycosis fungoides [36,37], multiple myeloma and Hodgkin's disease [38]. Certain infections and dermatological conditions have also been linked to this syndrome, namely lepromatous leprosy, leishmaniasis [39] and infectious mononucleosis [18].…”
Section: Sea-blue Histiocytosis Etiologymentioning
confidence: 99%